The Effects of Pesticide Use in Apple Orchards On Health and Reproduction of Cavity-nesting Birds - Bishop, Annette Christine (My University, 1998)
In southern Ontario, Canada during 1988-1997, pesticide exposure and its effects on the immune and endocrine systems and the behaviour and growth of tree swallos (Tachycineta bicolor) and on reproductive success in tree swallos and eastern bluebirds (Sailia sailis) were studied. Birds were exposed in sprayed apple orchards and non-sprayed sites. There were significant effects of pesticides on all of these endpoints. Sprayed tree swallow nestlings had significantly increased blastogenic response to pokeweed mitogen and delayed thymic maturation. Also, some tree swallow immune parameters were correlated to the date chicks were sampled. As the number of mixed sprays applied increased, there was a significant and positive increase in the concentration of the thyroid hormone, tri-iodo-thyronine, in male chicks and some indications of an increasing occurrence of a disrupted sertoli cell population on the seminiferous tubular basement membrane in testes. There were no effects of pesticides on adult swallow incubation times. There were significant increases in hunger signalling by tree swallow chicks after organophosphorus insecticide (OP) spray events in 1996 and 1997 and, after a second OP spray in 1996, there were significant decreases in the number of feeding trips by parent birds. However, weight of chicks did not vary among sites due to pesticide exposure. There was a significant increase in unhatched eggs in eastern bluebirds as organochlorine pesticide residues increased in eggs. At the gradient of contamination in tree swallow eggs, there were no trends between reproduction and organochlorines. With increasing toxicity and exposures to pesticides sprayed during 1988-1994, there were significant declines in egg fertility and daily survival rates of eggs and chicks of tree swallows and eastern bluebirds. Decreased reproductive rates were more often detected in tree swallows than in eastern bluebirds however the possibility that organochlorine chemicals contributed to these effects in bluebirds cannot be discounted.
Keywords: Biology; Biology